Síntese de 2-[5-Aril-3-(E-estir-1-il)-4,5-Diidro-1H-pirazol-1-il]-4-Fenil-6-Trifluormetilpirimidinas - Fiss, Gabriela Fehn (2005)
The synthesis of a series of 2-[5-aryl-3-(E-styr-1-yl)-4,5-dihydro-1H-pyrazol-1-yl]-4-phenyl-6-trifluoromethylpyrimidines (where aryl = C6H5, 2-MeC6H4, 2-MeOC6H4, 4-MeOC6H4, 3,4-(MeO)2C6H3, 3,4,5-(MeO)3C6H2, 4-ClC6H4) in 61-99% yields from the cyclocondensation reaction of 5-aryl-3-(E-styr-1-yl)-4,5-dihydro-1H-pyrazol-1-carboxamidines with 1,1,1-trifluoro-4-methoxy-4-phenyl-3-buten-2-one in the presence of catalytic amounts of BF3⋅OEt2, dichloromethane as solvent at room temperature (20-25 °C) for 15 minutes, is reported. The 5-aryl-3-(E-styr-1-yl)-4,5-dihydro-1H-pyrazol-1-carboxamidines were obtained from the cyclocondensation reaction of diarylideneacetones with aminoguanidine hydrochloride and triethylamine in ethanol under reflux for 24 hours.